Postactivation potentiation improves athletic performance without affecting plasma oxidative level - Gamberi, T.; Magherini, F.; Fiaschi, T.; Modesti, P. A.; Gulisano, M.; Marella, M.; Bosi, P.; Spicuglia, P.; Radini, M.; Modesti, A. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: Several authors reported evidences for postactivation potentiation (PAP) but so far, few studies suggested suitable methods for use it to improve performance. On the other hand, it is well known that a fatiguing exercise can leads to a temporary imbalance between the production of reactive oxygen species (ROS) and their disposal. The purpose of our research was to evaluate the effects on performance and plasma oxidative stress of a specific program of conditioning in replacement of traditional sequences of warm-up. METHODS: We proposed a protocol of specific conditioning exercises and the effect on performance is evaluated by measuring leg power using the counter movement jump performed at different time after the protocol in athletes trained for different sports. Moreover, we measured the antioxidant capacity and the plasma levels of reactive oxygen metabolites before and at different times after the conditioning. RESULTS: Considering the evaluation of explosive force of athletes subdivided for the different sports we noticed that the swimmer and tennis players do not show a significant improvement in it after conditioning while the soccer and rugby players shown a significant prolongation of the effect. Moreover, the analysis of oxidative stress shows that it is not influenced by the PAP protocol used. CONCLUSIONS: We can conclude that our specific protocol seems effective in improving performance in athletes who used training methods able to affect their explosive strength like soccer players. On the contrary, in our proposed program this effect seems to be less evident in athletes who used resistance-training programs.